2022
DOI: 10.3390/su14095161
|View full text |Cite
|
Sign up to set email alerts
|

Regional Division and Its Criteria of Mining Fractures Based on Overburden Critical Failure

Abstract: Mining fracture is the key factor in realizing water-conservation mining, stability evaluation of coal mining subsidence areas, and accurate restoration of the surface eco-environment. To clarify, the evolution and distribution of mining fractures, based on the key strata theory and the mining degree of overburden failure, the contact state of rock stratum after overburden critical failure was analyzed, the formation mechanism of “saddle shaped” water conducting fracture zone was revealed, and the permanent mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The formation of surface residual deformation mainly lies in the overburden gaps, and the distribution of overburden gaps mainly lies in the overburden failure and its structure [35]. Thus, the influencing factors of surface residual deformation are equivalent to that of overburden structure and caved zone, which also is the influence factors of overburden failure height.…”
Section: Influence Factorsmentioning
confidence: 97%
“…The formation of surface residual deformation mainly lies in the overburden gaps, and the distribution of overburden gaps mainly lies in the overburden failure and its structure [35]. Thus, the influencing factors of surface residual deformation are equivalent to that of overburden structure and caved zone, which also is the influence factors of overburden failure height.…”
Section: Influence Factorsmentioning
confidence: 97%
“…Meanwhile, with the panel continuous advances, the subsidence and separation occur only in the middle of bending zone. The contact state of the rock stratum interface will go through the process of point-to-surface, line-to-surface from the non-contact state to the surface-to-surface contact, and the separation will gradually reduce to the compaction state until the mining subsidence is transferred to the surface [ 39 ]. For ensuring the effectiveness of overburden grout injection and safe mining under buildings, backfilling slurry needs to be injected before the maximum development of separation space, and there must be a key stratum in the bending zone.…”
Section: The Mining Technology Of Grout Injection Into Overburdenmentioning
confidence: 99%
“…Many scholars have carried out research around this topic using to different theories. By analyzing the overburden failure and structure formation conditions, Bai et al (2022) proposed a regional division method and concluded that the residual surface deformation of a goaf was closely related to the mining time [14]. Xu et al (2023) evaluated the stability of a goaf through numerical simulations, and then classified the suitability of the site based on the simulation results and proposed different ecological restoration schemes [15].…”
Section: Introductionmentioning
confidence: 99%